2016
DOI: 10.1016/j.jpainsymman.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Children With Advanced Cancer: A Report From the PediQUEST Study

Abstract: Context Modifiable factors of health-related quality of life (HRQOL) are poorly described among children with advanced cancer. Symptom-distress may be an important factor for intervention. Objectives We aimed to describe patient-reported HRQOL and its relationship to symptom distress. Methods Prospective, longitudinal data from the multicenter Pediatric Quality of Life and Symptoms Technology (PediQUEST) study included primarily patient-reported symptom-distress and HRQOL, measured at most weekly with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
117
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 105 publications
(132 citation statements)
references
References 57 publications
6
117
0
9
Order By: Relevance
“…The Pediatric Quality of Life and Evaluation of Symptoms Technology (PediQUEST) study was developed to collect patient‐reported outcomes (PROs) in children with advanced cancer to better elicit the child’s voice around symptom experiences. Prior PediQUEST publications demonstrated that children with advanced cancer experience high symptom distress, and that symptom distress is strongly associated with health‐related QOL (HRQOL) . These data suggest that more intensive symptom management may improve a child’s HRQOL, and that identifying children at highest risk of symptom distress might facilitate interventions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pediatric Quality of Life and Evaluation of Symptoms Technology (PediQUEST) study was developed to collect patient‐reported outcomes (PROs) in children with advanced cancer to better elicit the child’s voice around symptom experiences. Prior PediQUEST publications demonstrated that children with advanced cancer experience high symptom distress, and that symptom distress is strongly associated with health‐related QOL (HRQOL) . These data suggest that more intensive symptom management may improve a child’s HRQOL, and that identifying children at highest risk of symptom distress might facilitate interventions .…”
Section: Introductionmentioning
confidence: 99%
“…Prior PediQUEST publications demonstrated that children with advanced cancer experience high symptom distress, and that symptom distress is strongly associated with health‐related QOL (HRQOL) . These data suggest that more intensive symptom management may improve a child’s HRQOL, and that identifying children at highest risk of symptom distress might facilitate interventions . To our knowledge, the impact of socioeconomic status on a child’s symptom distress and HRQOL has not been previously explored.…”
Section: Introductionmentioning
confidence: 99%
“…Patients reported a median of three concurrent distressing symptoms per survey; 73%, 35%, and 12% of patients reported at least two, five, and nine concurrent symptoms, respectively. 60 13 symptoms were independently associated with reductions in patient-reported health-related quality of life, which was further reduced when concurrent symptoms existed.…”
Section: Current Era Of Ppc Oncology Research (2010 To Present)mentioning
confidence: 94%
“…5458 In order to understand symptom burdens and health-related quality of life from the perspectives of children with advanced cancer (defined as progressive, recurrent, or non-responsive disease), investigators in the Paediatric Quality of Life and Symptoms Technology (PediQUEST) study 59,60 prospectively surveyed 104 children from three large children’s hospitals as often as once per week. Over a 9 month period, 920 surveys were collected, including 73 surveys of 25 children during their last 3 months of life.…”
Section: Current Era Of Ppc Oncology Research (2010 To Present)mentioning
confidence: 99%
“…The onset of a severe physical illness such as cancer, kidney, liver or gastrointestinal disease and the subsequent periods of hospitalisation are recognised as stressful life events for families and children . Dealing with such a severe illnesses on a daily basis has also led to increasing interest among paediatric healthcare professionals, to evaluate and foster the well‐being and quality of life among the children and their families.…”
Section: Introductionmentioning
confidence: 99%